1997
DOI: 10.1097/00004872-199715110-00004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of daily alcohol intake on the blood pressure differ depending on an individualʼs sensitivity to alcohol

Abstract: A repeated heavy alcohol intake could increase the risk of hypertension for Japanese subjects who exhibit skin flushing in response to alcohol consumption. Chronic alcohol intake by subjects with alcohol flushing might bring about a significant increase in blood acetaldehyde levels and cause an additional rise in the blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 20 publications
3
34
1
Order By: Relevance
“…Diastolic BP was suggested to be a little higher in the subjects having intact ALDH2, in contrast to the findings of Itoh et al 5 showing a higher BP in those inactive ALDH2. A higher BP in the drinkers with intact ALDH2 has also been observed in a previous study.…”
Section: Discussioncontrasting
confidence: 82%
See 4 more Smart Citations
“…Diastolic BP was suggested to be a little higher in the subjects having intact ALDH2, in contrast to the findings of Itoh et al 5 showing a higher BP in those inactive ALDH2. A higher BP in the drinkers with intact ALDH2 has also been observed in a previous study.…”
Section: Discussioncontrasting
confidence: 82%
“…The study of Itoh et al 5 however, showed only an indirect association of ALDH2 genotypes with higher BP in alcohol consumers, and it contradicted the negative findings in the previous two studies. 2,3 In addition, the genetic differences in the other ethanol metabolizing enzymes in Japanese, such as ADH2 and CYP2E1, have not been fully evaluated as related to BP elevation in drinkers, although both of them have been suggested to play a role in the development of alcoholic psychiatric [10][11][12] and liver diseases.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations